Development of a survey on the activity participation of children with special needs in preschool inclusive education - Xu, Li; Xiong, Zhiheng; Zeng, Li (Frontiers in Psychology, 2022)
participation refers to the individual's psychological and behavioral participation in activities. The activity participation of special children is an important index to measure preschool inclusive education. This study explores the preparation of a questionnaire suitable for the participation of special children in the inclusive education environment, so as to provide evaluation tools for researchers and teachers. The study includes the exploration of four dimensions of learning participation, life participation, teacher support and parental attitude of special children in inclusive education. The total dimension of the questionnaire’s Cronbach'sα coefficient is 0.950, Cronbach's of each sub dimensionα coefficient is between 0.916-0.981, and Mplus8.3 software is used to carries out confirmatory factor analysis on the four factor model. The standardized load of the four sub dimensions is between 0.88-0.95, the load reaches the significant level of 0.01, and the interpretation rate presents a medium and high level (the interpretation rate is greater than 70%), and the model fits well. Therefore, based on good reliability and validity, this questionnaire can be used to evaluate the activity participation of special children in preschool inclusive education.